2022
DOI: 10.1088/1742-6596/2177/1/012025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of real temperature data on the seasonal coefficient of performance of air source heat pumps

Abstract: In this paper, a transient analysis is performed in order to evaluate how effective climate data affect the determination of the seasonal coefficient of performance of ASHPs. Three Italian cities, characterized by different climates, are considered as reference case studies and the influence of real meteorological data, collected from different years, on the heat pump SCOP is performed. The analysis is carried out by employing the dynamic software TRNSYS. Numerical results show small variations in SCOP, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The analysis allowed the evaluation of the seasonal coefficient of performance, SCOP, defined as Comparison between the model proposed in [11] and the constant functions used in this analysis. Annual simulations were conducted, as in [10], considering the same building and the different heat pumps described in previous sections. Since the three considered municipalities are located in different climatic zones, the operating period of the heating system was assumed to be the standard period corresponding to each climatic zone, as explained in Table 1.…”
Section: Heatmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis allowed the evaluation of the seasonal coefficient of performance, SCOP, defined as Comparison between the model proposed in [11] and the constant functions used in this analysis. Annual simulations were conducted, as in [10], considering the same building and the different heat pumps described in previous sections. Since the three considered municipalities are located in different climatic zones, the operating period of the heating system was assumed to be the standard period corresponding to each climatic zone, as explained in Table 1.…”
Section: Heatmentioning
confidence: 99%
“…However, effective ambient temperature varies every year, and recently, climate change seems to lead to significant yearly variations. Indeed, the use of TRY might underestimate, or overestimate the effective energy performance of ASHP systems [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to market data [3], in Europe the most widespread typology of heat pumps employed in residential sector for heating and cooling are air source heat pumps, ASHP. The prevalence of ASHP is related basically to the availability of the air as heat source and to the limited installation cost respect to other types of heat pumps as for example ground source heat pumps [4,5]; air source heat pumps, on the other hand, are characterized by reduced performances with respect to ground source heat pumps, and their performance strongly depends on weather conditions and frost formation on the external evaporator, as suggested in many papers in the literature [6][7][8]. The transition towards more sustainable energy sources in building heating, however, should not overlook the importance of thermal comfort and indoor air quality.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Beccali et al [8] remarked that climate can influence the performance of a heat pump. As demonstrated by many researchers [10][11][12], the climatic and installation conditions affect the entire system's performance. Carrol et al [10] found three main areas of focus within this framework: defrosting management, ASHP system management and ASHPs as smart grid demand response components.…”
Section: Introductionmentioning
confidence: 99%